Performance Study of E-Nose Measurement Chamber for Environmental Odour Monitoring - G. Viccione; T. Zarra; S. Giuliani; V. Naddeo; V. Belgiorno (Chemical Engineering Transactions, 2012)
Offensive odours from industrial and sanitary environmental engineering plants can cause problems, such as sleep disorders, migraine and loss of appetite, also considering that they address the quality of life. Odour emission characterization is currently discussed in international literature as to determine its most feasible implementation. A method for continuous odour monitoring is based on the use of electronic noses. Electronic nose is an instrument which comprises an array of electronic chemical sensors with partial specificity and an appropriate pattern recognition system, capable of recognizing simple or complex odours. Aim of this work is to numerically analyze the performance of a sensor chamber in order to improve sensor response signals in terms of stability, reproducibility and response time. Comparative results are based on the location of four different diffusers. The numerical analysis was performed by a computational fluid dynamic (CFD) software in order to guarantee that all sensors are exposed to the same chemical sample under the same experimental conditions for the same time, reducing the presence of stagnant or recirculating regions.